Ancaman Siber Internasional : Lazarus Group sebagai Instrumen Perang Asimetris Korea Utara - Rika Sartika; Nur Isdah Idris (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The advancement of digital technology has made cyberspace a new arena for international conflict. The Lazarus Group, a hacking group allegedly affiliated with the North Korean government, has come to global attention for its involvement in numerous large-scale cyberattacks targeting financial institutions, global corporations, and public infrastructure. This study aims to analyze the group's operational patterns, strategic motives, and its implications for global cybersecurity. Using a qualitative approach and document analysis, the study investigates how Lazarus represents North Korea's strategy to counter international isolation and gain economic advantage. The results show that the international community's response to state actor threats in cyberspace is fragmented and ineffective. Therefore, a stronger and more coordinated multilateral framework is needed to respond to cyber threats from state actors.